(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
Theoretical and technological aspects of the formation of professional mobility of graduates of technical universities are considered. The main characteristics and content of professional mobility have been identified. The factors influencing the formation of professional mobility are considered